The first studies in marketing: context, institutionalization and method - Oliveira, Sergio Luis Ignacio (Circumscribere International Journal for the History of Science, 2009)
This study discusses the philosophical and scientific methods used by the first marketing theoreticians of the beginning of the twentieth century, the importance of the context in the first studies of the area and its institutionalization process